A novel small RNA regulates Locus of Enterocyte Effacement and site-specific colonization of enterohemorrhagic Escherichia coli O157:H7 in gut - Han, Runhua; Qian, Ye; Zheng, Chenguang (Frontiers in Cellular and Infection Microbiology, 2025)
Enterohemorrhagic Escherichia coli (EHEC) is a contagious foodborne pathogen that specifically colonizes the human large intestine, which is regulated by different environmental stimuli within the gut. Transcriptional regulation of EHEC virulence and infection has been extensively studied, while the posttranscriptional regulation of these processes by small RNAs (sRNAs) remains not fully understood. Here we present a virulence-regulating pathway in EHEC O157:H7, in which the sRNA EvrS binds to and destabilizes the mRNA of Z2269, a novel transcriptional regulator. In turn, Z2269 indirectly activates the expression of LEE (locus of enterocyte effacement) pathogenicity island through the master regulator Ler. Importantly, the expression of EvrS is modulated by environmental oxygen levels. EvrS also exhibits lower expression in the colon compared to the ileum, influencing the site-specific colonization of EHEC O157:H7 in mice. These results indicate that the oxygen status within the intestine may regulate the expression of EvrS, thereby modulating virulence factors of EHEC and contributing to successful infection in vivo. This study has broader implications for understanding sRNA functions in spatiotemporal virulence control of EHEC and may provide novel strategies to prevent EHEC infections.